Supranormal stimulation of deoxyribonucleic acid synthesis in FRTL5 cells by serum from patients with untreated acromegaly - Misaki, T; Maciel, R M; Tramontano, D; Moses, A C; Lombardi, A; Ingbar, S H (The journal of clinical endocrinology and metabolism, 1988)
Insulin-like growth factor I (IGF-I) is one of a number of mitogenic factors in the serum of animals and humans. We demonstrated previously that IGF-I is a potent mitogen for FRTL5 cells, a line of rat thyroid follicular cells. In this study, we assessed the relevance of this finding with respect to the levels of IGF-I found in human serum by comparing the effects of normal serum and serum from patients with untreated acromegaly or hypopituitarism on DNA synthesis in quiescent FRTL5 cells. As expected, when added to cells maintained in Coon's modified Ham's F-12 medium containing 0.1% BSA, but devoid of insulin, transferrin, TSH, or calf serum, normal serum produced a dose-dependent stimulation of [3H]thymidine incorporation into DNA. A similar, but more marked, effect was produced by the addition of serum from patients with untreated acromegaly. In multiple experiments, a standard concentration (0.5%) of acromegaly serum was more stimulatory to DNA synthesis than was normal serum. In a single experiment designed to eliminate interassay variation and define the relationship between the ability of serum to stimulate DNA synthesis and its IGF-I concentration, studies were performed with 0.5% concentrations of serum from 9 normal subjects, 15 patients with untreated acromegaly, and 3 patients with panhypopituitarism. On the average, [3H]thymidine incorporation in the presence of serum from patients with acromegaly was approximately 3 times, and that in the presence of serum from patients with hypopituitarism only one fourth, that in the presence of serum from normal subjects; there was no overlap of individual values in the three groups. For the entire study group, we found a highly significant correlation (r = 0.86) between the serum IGF-I concentration and the ability of that serum to stimulate thymidine incorporation into the DNA of FRTL5 cells. The stimulatory effects of serum from both normal and acromegalic subjects were decreased or abolished by the addition of a monoclonal antibody against IGF-I. In hypophysectomized rats, GH increases the thyroid to body weight ratio and enhances the effect of TSH to promote thyroid growth. Further, an inordinate frequency of nontoxic goiter in patients with acromegaly has been reported. Taken together with these observations, our findings suggest that the effect of IGF-I to promote thyroid cell growth in vitro has a counterpart in the living animal or patient.